Paxillin Is Required for Androgen Receptor Expression in Granulosa Cells - Astapova, Olga (J Endocr Soc, 2021)
Androgens are important in female reproduction, as evident from studies of mouse ovary-specific androgen receptor knockout models characterized by sub-fertility and diminished ovarian reserve. Androgen activity specifically promotes granulosa cell proliferation and follicle progression. However, the molecular mechanisms mediating androgen activity in granulosa cells are unknown. Our lab previously showed that the cytoplasmic adaptor protein paxillin is required for full transcriptional activity by the androgen receptor (AR) in prostate cancer cells, therefore we examined how paxillin affects the androgen receptor in granulosa cells. We found that paxillin knockdown results in significantly reduced AR protein levels, independently of AR gene transcription in human granulosa-derived KGN cells. Similar to previous data from other cell types, we found that paxillin directly interacts with poly-A binding protein (PABP) in KGN cells using proximity ligation assay. Ligand binding further increases AR protein expression by reducing its degradation. Using immunofluorescence, we confirm that in both KGN and primary mouse granulosa cells, similarly to the prostate, ligand-bound AR is primarily localized in the nucleus. Based on this and previous studies, we propose that paxillin enhances AR mRNA translation through interaction with PABP, and ligand binding further increases AR protein level by nuclear retention, protecting from degradation in the cytoplasm. Our findings highlight a previously unrecognized role of paxillin in granulosa cells, where it may be an important target for modulating androgen activity in androgen-related disorders of female reproduction.